The Attitudes of Students and Teachers toward the Use of Interactive Whiteboard (IWB) in Education: Case of Computer Engineering Department at Eastern Mediterranean University - Ranjbar, Mohammad Mehdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
The aim of this study was to examine teachers’ and students’ attitudes of interactive whiteboards (IWBs) as an instructional tool in computer engineering classrooms and to find out potential differences in attitudes according to some variables such as gender, age, hours of weekly IWB use, years of study and years of teaching experience of the participants. For data collection, both quantitative and qualitative methods were used. Two questionnaires distributed to 40 teachers and 150 students and also 10 teachers were interviewed to explore their opinions towards the use of IWB in the Department of Computer Engineering at Eastern Mediterranean University (EMU). The findings of this research indicated that the attitudes of teachers and students about using of IWBs technology in education were positive because they were mindful of the benefits of this technology in promoting meaningful teaching and learning. The result of the study has shown that there are statistically significant differences between the attitudes of students and teachers towards IWB use in their studies. It was also found that most teachers believe that IWB constitutes an effective and convenient way to deliver the learning content and that it increases the level of classroom interaction which in turn facilitates the learning experience, and also teachers expressed that they need training programs to acquire the essential competencies required to use this technology efficiently. Furthermore, the results showed that when students were involved in the IWB-base lessons their attitudes towards new technology have changed to more positive over time and this fluctuation in attitudes can be easily captured when dealing with and manipulating IWBs. Keywords: Interactive whiteboard; Teachers’ Attitudes; Students’ attitudes; ICT

ÖZ: Bu çalışmanın amacı, bilgisayar mühendisliği sınıflarında bir ders anlatım aracı olarak kullanılan akıllı tahtaların (IWB); cinsiyet, yaş, akıllı tahtaların haftalık kullanım saatleri, öğrencilerin öğrenim gördükleri süre ve akademisyenlerin akademisyenlik yapmış oldukları süre gibi kriterlere göre, katılımcı akademisyen ve öğrencilerin tavırlarının gösterebileceği farklılıkları incelemektir. Bilgi toplarken, nicel ve nitel teknikler kullanılmıştır. Kullanılan iki anket, 40 akademisyen ve 150 öğrenci tarafından doldurulmuş ve Doğu Akdeniz Üniversitesi (DAÜ) Bilgisayar Mühendisliği bölümünden 10 akademisyen de akıllı tahtalara olan bakışları incelenebilsin diye bire bir görüşmeye tabi tutulmuştur. Bu çalışmada, eğitimde teknolojinin sağladığı faydaların farkında olan akademisyen ve öğrencilerin akıllı tahta kullanımına olan pozitif yaklaşımları gözlemlenmiştir. Çalışmanın bir diğer sonucu ise öğrenci ve akademisyenlerin akıllı tahtaların eğitimdeki kullanımına olan yaklaşımlarındaki istatiksel farklılıklardır. Birçok akademisyenin, akıllı tahtaların etkili ve uygun bir öğretim sunmaya olanak sağladığını, derse olan ilgiyi arttırdığını, öğretimi kolaylaştıran bir gereç olduğunu düşündüğü anlaşılmış ve aynı zamanda akademisyenler, bu teknolojiyi etkin bir şekilde kullanabilmek için eğitim alınması gerektiğini de vurgulamışlardır. Buna ek olarak, öğrenciler akıllı tahta kullanımının uygulandığı derslere katıldıkça, zaman içinde yeni teknolojiye olan tavırlarının pozitif yönde değiştiği sonucuna ulaşılmış ve aynı zamanda bu değişim, öğrenciler akıllı tahtaları kullanılırken de rahatça gözlemlenilmiştir. Anahtar Kelimeler: İnteraktif beyaz tahta; Öğretmen Tutumları; Öğrencilerin tutumları; BİT
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer and Instructional Technology Teacher Education, 2016. Supervisor: Dr. Fatma Tansu Hocanın.
Keywords: Computer and Instructional Technology Teacher Education; Information and Communication Technologies in Education; Education - Computer network resources; Distance Education; Educational Technology-Student Attitudes; Teaching - Computer network resources; Interactive whiteboard; Teachers’ Attitudes; Students’ attitudes; ICT